Answer:
90/23
Step-by-step explanation:
First, you want to start in the parentheses. 5-6=-1, then multiply it by -2. Since a negative multiplied by a negative is a positive, -2*-1=2. -3^2=-9. 2+8=10. Then -9 times 10= -90. Then, we move on to the bottom. 5--2=7. 4^2=16, and -2(2)=-4. So -5(7) + 16-4=-23. Now, the equation should look like this, -90/-23. Put the negatives together and you get 90/23.
Answer:
Step-by-step explanation:
<u>Given points:</u>
- A(-1, -9) and M(0.5, -2.5)
Let the coordinates of B are (x, y)
<u>Use midpoint formula to determine the point B:</u>
- 0.5 = (- 1 + x)/2 ⇒ 1 = -1 + x ⇒ x = 1 + 1 = 2
- -2.5 = (-9 + y)/2 ⇒ -5 = -9 + y ⇒ y = -5 + 9 = 4
Answer:
x = -3 and x = -3/2
Step-by-step explanation:
After writing down the polynomial, split it; put a line between 3x^2 and -18x. Look and 2x^3 + 3x^2 and -18x - 27 separately and factor them both:
p(x) = 2x^3 + 3x^2 <u>- 18x -27</u>
p(x) = x^2(2x+3) <u>-9(2x+3)</u>
Now notice how x^2 and -9 have the same factor (2x+3). That means x^2 and -9 can go together:
p(x) = (x^2 - 9)(2x+3)
Factor it once more because there's a difference of squares:
p(x) = (x+3)(x-3)(2x+3)
Now just plug in whatever makes the each bracket equal 0:
x = -3, x = 3, and x = -3/2
Those are your zeros.
Answer:
The greatest common factor is 10
Step-by-step explanation:
Once you factor it out, you have :
10(x^2+5)